Time-Dependent Induction of Hepatic Cytochrome P450 Enzyme Activity and mRNA Expression by Bilobalide in Rats - Yuko Taki; Yuko Yamazaki; Fumio Shimura; Shizuo Yamada; Keizo Umegaki (Elsevier, 2009)
A single dose by gavage of bilobalide (30 mg/kg) was found to produce a time-dependent induction of hepatic cytochrome P450 (CYP) enzyme activity and protein expression in rats. An RT-PCR study further showed that mRNA expression of CYP2B was maximal at 6 h. Plasma and liver bilobalide concentration in rats following administration of Ginkgo biloba extract equivalent to bilobalide of approximately 40 mg/kg showed a similar response to that exhibited by mRNA expression. These findings suggest that bilobalide markedly induced hepatic CYPs, but the induction could be mitigated due to rapid elimination from the liver. Keywords:: bilobalide, cytochrome P450 (CYP) induction, herb-drug interaction